Epidermodysplasia verruciformis: a rare case presentation - Prateek, Kumar; Chaudhary, Shyam Sundar; Sachan, Sonal; Sahu, Yuvraj; Choubey, Pooja (Journal of Pakistan Association of Dermatologists, 2017)
Epidermodysplasia verruciformis (EV) is a rare genodermatosis characterized by a unique susceptibility to cutaneous infection by a group of phylogenetically related human papilloma viruses (HPVs). These patients show a defect in cell-mediated immunity specific toward the causative HPVs that leads to lifelong disease. The defect is usually inherited as autosomal recessive trait and presents clinically with plane warts, pityriasis versicolor-like lesions and reddish verrucous plaques. Dysplastic and malignant changes in the form of actinic keratoses, Bowen's disease and squamous cell carcinoma (SCC) are common but metastasis occurs rarely. A totally effective treatment against EV is as yet highly desirable. We report a case of EDV in a 13-year-old female patient with confluent wart like lesions, pityriasis versicolor like lesions and reddish plaques. The case is being reported in view of rarity of disease. Â 